Written correspondence: Challenges and adjustments of BACOM students in online learning (ELT Forum: Journal of English Language Teaching, 2022)
The sudden shift from traditional to online learning because of the COVID-19 pandemic has made written communication the primary method for students and instructors to send and receive information. However, most students still experience challenges when communicating with their instructors in written form, especially first-year university students. Henceforth, this study aimed to understand the written communication challenges of freshman Bachelor of Arts in Communication (BACOM) students of S.Y. 2020-2021. Specifically, the study intended to determine the challenges encountered by the participants in written correspondence with their instructors in terms of online learning, the consequences of the challenges identified, and the ways to improve written communication between the participants and their instructors. This qualitative study used Hermeneutic Phenomenology in one state university in Cordillera Administrative Region, Philippines. Data was gathered through an online focus group interview which was analyzed using Reflexive Thematic Analysis. Findings of the study show that the major challenges endured by the students are uncertainty, sensitivity, comprehension deficit, poor internet connection, and grammar inaccuracies. As a result of these difficulties, the outcomes identified by the students are delayed inquiries, poor performance, low self-esteem, and a communication gap. Based on the students' suggestions, effective written communication can be improved between instructors and students by employing empathy, online etiquette, systematized platform, initiative, feedback, cooperation, clarity of instructions, clarity of concerns, and open communication. Chiefly, this study demonstrates that both students and instructors should be aware of their respective roles and duties to establish healthy, productive, and effective learning and communication now that the learning system has shifted online.